2009
DOI: 10.1016/j.ajhg.2009.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Muscular Atrophy with Pontocerebellar Hypoplasia Is Caused by a Mutation in the VRK1 Gene

Abstract: The spinal muscular atrophies (SMAs) are a genetically and clinically heterogeneous group of disorders characterized by degeneration and loss of anterior horn cells in the spinal cord, leading to muscle weakness and atrophy. Spinal muscular atrophy with pontocerebellar hypoplasia (SMA-PCH, also known as pontocerebellar hypoplasia type 1 [PCH1]) is one of the rare infantile SMA variants that include additional clinical manifestations, and its genetic basis is unknown. We used a homozygosity mapping and position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
162
2
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(174 citation statements)
references
References 28 publications
4
162
2
4
Order By: Relevance
“…Its D. melanogaster ortholog, NHK-1, also affects meiotic recombination (72). Recently a recessive mutation in VRK1, R385X, manifested a complex syndrome with a pontocerebellar hypoplasia, ataxia, and muscular atrophy (73). Although the pathogenic role of VRK1 in this clinical report is not clear, it is interesting to note that patients with mutations in other kinases, like ATM and ATR, also present motor coordination problems and ataxia (1).…”
Section: Discussionmentioning
confidence: 82%
“…Its D. melanogaster ortholog, NHK-1, also affects meiotic recombination (72). Recently a recessive mutation in VRK1, R385X, manifested a complex syndrome with a pontocerebellar hypoplasia, ataxia, and muscular atrophy (73). Although the pathogenic role of VRK1 in this clinical report is not clear, it is interesting to note that patients with mutations in other kinases, like ATM and ATR, also present motor coordination problems and ataxia (1).…”
Section: Discussionmentioning
confidence: 82%
“…Defects in these genes are associated with several forms of myopathies (41), including limb-girdle muscular dystrophy 2F, which causes limb musculature wasting and locomotory troubles in juvenile individuals. Additionally, many selected genes are involved in balance and motor coordination, including VRK1 and TCTN1, with defects associated with underdevelopment of the cerebellum, motor dysfunction and muscle hypotonia (42,43), and CNTN6, loss of which causes motor coordination and equilibrium impairment in KO mice (44). This set of genes also includes a member of the collagen protein family, COL22A1, which localizes to myotendinous and articular junctions (45).…”
Section: Resultsmentioning
confidence: 99%
“…S2A and B) and we found that a change in the charge in this region resulted in increased binding. Noteworthy, when the mutation that causes spinal muscular atrophy, VRK1(R358X) [50], was tested we showed that VRK1 was still able to interact with p53 ( Fig. S2A and B).…”
Section: Vrk1 Stably Interacts With P53 Forming a Basal Protein Complexmentioning
confidence: 99%